Pembelajaran Holistik, Kontekstual dan Futuristik - Taufiqurrahman, Taufiqurrahman; Widyaningsih, Erna; Dewi, Rachma Rusdiana (Lembaga Yasin AlSys, 2025)
Holistic, contextual, and futuristic learning is an educational concept that emphasizes the integration of intellectual, emotional, social, and technological aspects in the learning process. The holistic approach aims to develop students' potential comprehensively, while contextual learning ensures that the material studied is relevant to everyday life. Meanwhile, futuristic learning focuses on innovation and technological advancements to prepare students for future challenges. This article examines the application of these three approaches in modern education systems and the challenges faced in their implementation. By adopting an integrated learning strategy, students are expected to gain deeper understanding and skills that align with contemporary demands.